DETERMINATION OF THE GENETIC VARIATION AMONG SOME TURKISH RICE (OR YZA SATIVA L.) C ULTIVARS USING ISSR TECHNIQUE - B. Törün; E. Sözen (Journal of Animal and Plant Sciences, 2018)
In this study, the genetic diversity levels of 28 different rice varieties developed in Turkey were determined by using ISSR markers. Twenty different ISSR primers amplified 268 bands of which 217 were polymorphic. Band number for each primer ranged from 5-22 with an average number of 13.4. Polymorphism percentages varied between 40.00% and 94.12% with an average of 80.97%. Polymorphism Information Content (PIC) values were between 0.274 and 0.374 with an average value of 0.347. Similarity values indicated that the most similar varieties were Efe and Hamzadere (0.856) and the least similar varieties were Demir and Bafra Y1ld1z1 (0.395)U. PGMA analysis grouped 28 rice varieties into two main clusters and showed that genotypes obtained from same institute tend to cluster together. This implies the possibility of natural cross pollination between rice varieties grown in close fields. Our results indicated that ISSR technique is effective to study genetic variation in Turkish rice cultivars. Data obtained from this study could be used in the rice improvement programs. increase the speed and precision of breeding programs
Keywords: Rice; Genetic variability; Inter Simple Sequence Repeats.